Biodiversity Checklist of Senga Dollfus, 1934 (Pseudophyllidea: Ptychobothriidae) Species from Different Piscine Hosts - Madan, Zeenat; Upadhyay, Sushil Kumar; Singh, Manoj; Yadav, Mukesh; Yadav, Deepak (Asian Journal of Biological and Life Sciences, 2026)
The genus Senga Dollfus, 1934, belonging to the order Pseudophyllidea and family Ptychobothriidae, comprises a distinctive group of intestinal cestodes parasitizing freshwater teleost fishes. This genus was first established with the description of Senga besnardi from Betta splendens in Vincennes, France. Members of Senga exhibit unique morphological features, including a dorsoventrally flattened, elongated and segmented body (strobila), a specialized anterior scolex for attachment and hermaphroditic reproductive systems within each proglottid. These adaptations facilitate their survival and reproduction within the intestinal tracts of fish hosts. Over time, Senga species have been reported from a diverse range of fish hosts, particularly from Mastacembelus armatus, Channa punctatus, Channa striatus, Channa micropeltes, Mystus vittatus, Rita rita, Puntis ticto and Labeo rohita from India and abroad. Since the initial discovery, numerous species have been described globally, particularly across tropical Asian regions. The present review provides a comprehensive and critically evaluated checklist of 68 valid species of Senga, compiled from various geographic locations and fish hosts. This review paper provides the insights into immense diversity of the genus Senga across different hosts, locations and habitats thus provides a useful base for future studies in parasitology, taxonomy and freshwater ecology.
Keywords: Helminthes; Cestodes; Parasites; Senga; Fishes; Biodiversity